Mitochondria-rough-ER contacts in the liver regulate systemic lipid homeostasis - Anastasia, Irene; Ilacqua, Nicolò; Raimondi, Andrea; Lemieux, Philippe; Ghandehari-Alavijeh, Rana; Faure, Guilhem; Mekhedov, Sergei L.; Williams, Kevin J.; Caicci, Federico; Valle, Giorgio; Giacomello, Marta; Quiroga, Ariel D.; et al. (Cell reports (Cambridge), 2021)
Contacts between organelles create microdomains that play major roles in regulating key intracellular activities and signaling pathways, but whether they also regulate systemic functions remains unknown. Here, we report the ultrastructural organization and dynamics of the inter-organellar contact established by sheets of curved rough endoplasmic reticulum closely wrapped around the mitochondria (wrappER). To elucidate the in vivo function of this contact, mouse liver fractions enriched in wrappER-associated mitochondria are analyzed by transcriptomics, proteomics, and lipidomics. The biochemical signature of the wrappER points to a role in the biogenesis of very-low-density lipoproteins (VLDL). Altering wrappER-mitochondria contacts curtails VLDL secretion and increases hepatic fatty acids, lipid droplets, and neutral lipid content. Conversely, acute liver-specific ablation of Mttp, the most upstream regulator of VLDL biogenesis, recapitulates this hepatic dyslipidemia phenotype and promotes remodeling of the wrappER-mitochondria contact. The discovery that liver wrappER-mitochondria contacts participate in VLDL biology suggests an involvement of inter-organelle contacts in systemic lipid homeostasis. [Display omitted] •Liver mitochondria are extensively wrapped by curved sheets of rough ER (wrappER)•The wrappER is enriched in fatty acid and VLDL transcripts, proteins, and particles•WrappER-mitochondria contacts regulate VLDL synthesis and respond to lipid flux changes•WrappER-mitochondria contacts contain MAMs and sites of adhesion between organelles Anastasia et al. characterize the contact established by a curved wrapping-type of rough ER (wrappER) with mitochondria and discover that this inter-organellar association is dynamic, regulated by lipid fluxes, and necessary for correct hepatic synthesis and secretion of very-low-density lipoproteins.